Marine Spatial Allocations of the Coastal and Small Islands Zoning Plan in West Sumatera Province - Suparno, Suparno; Arlius, Arlius; Efriyeldi, Efriyeldi; Putra, Aprizon (Sumatra Journal of Disaster, Geography and Geography Education, 2022)
The Coastal and Small Islands Zoning Plan (RZWP3K) is a plan that determines the direction of utilization of the resources of each planning unit is accompanied by the determination of the structure and spatial patterns in the planning regions. The purpose of this research is to analyze the marine spatial allocations and utilization arrangement of RZWP3K in West Sumatra Province. The research method used is the analysis of environmental suitability criteria is done through the procedures of Geographic Information System (GIS) in the form of overlap parameters biophysical of coastal/marine waters. Spatial utilization arrangements are based on the procedure for the preparation of the RZWP3K and the Minister of Marine and Fisheries regulations of the Republic of Indonesia (Permen KP) No. 23/2016. Results of the analysis of the RZWP3K in West Sumatra Province divided into 4 regions, i.e general utilization, conservation, certain national strategic, and cruise groove. General utilization (3,041,610, 20 ha) consist of tourism, port, capture fisheries, aquaculture, mangrove, industrial, public facility, and other utilization. Conservation (196,905.34 ha) consist of conservation of waters, coastal, and small islands. Certain national strategic regions (331,683.99 ha) consist of defence and security zones. RZWP3K are important documents of the Provincial Government in Indonesia as the basis for the business permit granting in waters (marine).